Energy contents of the wormholes - Ulu Doğru, Meli̇s; Türkoğlu, Murat (World Scientific Pub Co Pte Lt, 2011)
In this study, energy distributions of the various wormholes which connect two different parts of the universe have been investigated. We have obtained the energies of several types of wormholes as the statical wormholes, wormholes with scalar fields, electrical charged wormholes, zero density wormholes, zero radial tides wormholes, conformal wormholes, inflating wormholes, wormhole model in the Friedmann–Robertson–Walker (FRW) cosmology and Visser–Kar–Dadlich (VKD) wormholes using the Einstein, Weinberg and Landau–Lifshitz energy–momentum prescriptions. The Weinberg and Landau–Lifshitz energies of the statical wormholes, wormholes with scalar fields, electrical charged wormholes, zero density wormholes, zero radial tides wormholes or VKD-wormholes give the same results. Also, Weinberg, Landau–Lifshitz and Einstein energies of the conformal wormholes, inflating wormholes or wormholes in the FRW-cosmology give the different results.
Keywords: energy-momentum complexes; general relativity; wormholes; Relativistic cosmology